Ultra-small molybdenum-based nanodots as an antioxidant platform for effective treatment of periodontal disease - Chen, Li; Zhao, Tianjiao; Liu, Min; Chen, Qiaohui; Yang, Yunrong; Zhang, Jinping; Wang, Shuya; Zhu, Xiaoyu; Zhang, Huanan; Huang, Qiong; Ai, Kelong (Frontiers in Bioengineering and Biotechnology, 2022)
Periodontal disease (PD) is a local inflammatory disease with high morbidity, manifesting tissue destruction results from inflammation of host immune response to bacterial antigens and irritants The supportive function of connective tissue and skeletal can be jeopardized without prompt and effective intervention, representing the major cause of tooth loss. However, traditional treatments exhibited great limitations, such as low efficacies, causing serious side effects and recurrent inflammatory episode. As major defense mechanism, reactive oxygen species (ROS), play important roles in the pathological progression of PD. Antioxidant therapy is widely believed to be as an effective strategy for ROS-triggered diseases, including oxidative stress-induced PD. Most antioxidants can only scavenge one or a few limited kinds of ROS and cannot handle all kinds.. In addition, current antioxidant nanomaterials present limitations associated with toxicity, low stability and poor biocompatibility. To this end, we develop an ultra-small Molybdenum-based nanodots (MoNDs) with strong ROS in oxidative stress-induced PD. To our knowledge, this is the first time that MoNDs has been used for PD. In the present study, MoNDs has shown extremely good therapeutic effects as ROS scavengers. Spectroscopic and in vitro experiments provided strong evidences for the roles of MoNDs in eliminating multiple ROS and inhibiting ROS-induced inflammatory responses. Besides, the mouse model of PD was established and demonstrates the feasibility of MoNDs as powerful antioxidants. It can alleviate periodontal inflammation by scavenging multiple ROS without obvious side effects and exhibit good biocompatibility. Thus, this newly developed nanomedicine is effective in scavenging ROS and inhibiting M1 phenotypic polarization, which provides promising candidates for the treatment of PD.